Understanding the direct and indirect impacts of disease response phenotypes on chicken coccidiosis epidemiology: A modelling approach - Marie Ithurbide; Marie-Hélène Pinard van der Laan; Yuqi Gao; Andries D. Hulst; Mart C.M. De Jong; Andrea Doeschl-Wilson (PLoS ONE, 2026)
Coccidiosis, a widespread disease in poultry caused by protozoan parasites of the genus Eimeria, leads to significant economic losses. The increasing resistance of Eimeria species to anti-parasitics, combined with the high cost of vaccines, underscores the need for alternative intervention strategies against coccidiosis. This article explores the relative impact of several traits on the health of the group, accounting for the population dynamics of the infection. We focus on five traits that can potentially be influenced by genetic selection, treatment, vaccination or nutrition: (1) susceptibility, (2) recoverability, (3) infectivity, (4) tolerance, and (5) compensatory growth occurring after the infection ends. We propose an epidemiological model of coccidiosis based on literature review concerning chicken coccidiosis epidemiology and parameter estimations based on published data. Using this model, we investigate the direct and indirect impacts of each individual trait on the health and productivity of the flock. This approach aims at understanding the relative role of these individual traits on population level disease resistance and economical profitability of farms undergoing coccidiosis epidemics. The results showed increasing recoverability and tolerance were particularly beneficial for the health and productivity of the flock, both through direct and indirect effects whilst reducing infectivity has the highest beneficial effect on reducing the infectious load in the environment and on flock level protection. This approach has the potential to guide disease control strategies aimed at enhancing coccidiosis management within the poultry industry.